1997
DOI: 10.1093/carcin/18.4.795
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]pyrene up-regulates cyclooxygenase-2 gene expression in oral epithelial cells

Abstract: Cyclooxygenase may be important in the pathogenesis of smoking-related cancer because it activates carcinogens and catalyzes prostaglandin biosynthesis. We determined the effects of benzo[a]pyrene (B[a]P), a polycyclic aromatic hydrocarbon in tobacco smoke, on cyclooxygenase-2 (Cox-2) mRNA, protein and synthesis of prostaglandin E2 (PGE2) in normal and transformed oral epithelial cells. Treatment with B[a]P caused a dose-dependent increase in production of PGE2, with a maximal increase of approximately 100%. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(61 citation statements)
references
References 21 publications
2
59
0
Order By: Relevance
“…4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), a nicotine-nitrosated derivative, is the major carcinogenic component in cigarette smoke. Since the polycyclic aromatic hydrocarbon of tobacco smoke was reported to cause an increase in cyclooxygenase-2 (COX-2) and its downstream product prostaglandin E 2 in normal and transformed oral epithelial cells in 1997 (Kelley et al, 1997), an interest in the role of COX-2 and its metabolites in tobacco carcinogen-related carcinoma has been increased.…”
Section: Introductionmentioning
confidence: 99%
“…4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), a nicotine-nitrosated derivative, is the major carcinogenic component in cigarette smoke. Since the polycyclic aromatic hydrocarbon of tobacco smoke was reported to cause an increase in cyclooxygenase-2 (COX-2) and its downstream product prostaglandin E 2 in normal and transformed oral epithelial cells in 1997 (Kelley et al, 1997), an interest in the role of COX-2 and its metabolites in tobacco carcinogen-related carcinoma has been increased.…”
Section: Introductionmentioning
confidence: 99%
“…The COX-2 gene is an earlyresponse gene that is up-regulated by proinflammatory stimuli, growth factors, oncogenes, carcinogens, and tumor-promoting phorbol esters. 4,5 Previous studies have suggested that COX-2 plays a role in carcinogenesis. Several epidemiologic investigations have reported a lower than expected rate of colorectal adenomas and carcinomas in persons taking nonsteroidal antiinflammatory drugs (NSAIDs), inhibitors of cyclooxygenase activity.…”
mentioning
confidence: 99%
“…COX-1 is expressed constitutively in most tissues and may be responsible for housekeeping functions (4). In contrast, COX-2 is not detectable in most normal tissues or resting immune cells, but its expression can be induced by endotoxin, cytokines, growth factors, and carcinogens (5)(6)(7).…”
mentioning
confidence: 99%